UJI AKTIVITAS ANTIHIPERLIPIDEMIA DAN ANTIATEROSKLEROSIS ISOLAT ANDROGRAFOLID DAN EKSTRAK TERPURIFIKASI HERBA SAMBILOTO (Andrographis paniculata (Burm.f) Ness) PADA TIKUS DIABETES MELLITUS TIPE 2 RESISTEN INSULIN - , NI KADEK WARDITIANI, Dr. Agung Endro Nugroho, M.Si., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Diabetes mellitus (DM) is a degeneratif disorder that highly happens in Indonesia community due to increasing blood sugar level above normal level. Insulin resistance type 2 DM is one of type 2 DM that marked not only by hyperglicemia but also hyperlipidemia (LDL, triglyceride and cholesterol level increases in bloods). The main objective of this investigation is to antihyperlipidemia and antiatherosclerosis activity of andrographolide (1.5 and 4.5 mg/kg bw twice daily) and purified extract of bitter herb (434.6 and 1303.8 mg/kg bw) in insulin resitance type 2 DM rat and also influence of fructose 1,8 g/kg bw and food high fat (15% lard and 5% yolk) will made plaque in vein rat. First step was to isolation andrographolide and to make purified extract bitter herb. Insulin resistant type 2 rat was prepared by inducing with fructose 1.8 g/kg bw and high fat food for 50 days. Andrographolide and purified extract were given for 5 days after that treatment, and then measure lipid level in bloods (LDL, triglyceride and cholesterol), last take aorta organ for atherosclerosis test. By HPLC analysis the purity of andrographolide (88.29 Â± 1.94)% was found. By HPTLC analysis the purity of purified extract (16.13 Â± 0.50)% was found. On other hand, administration of fructose and high fat food for 50 days has brought about plaque fat in vein rat. Administration andrographolide and purified extract of bitter herb decreased blood LDL and triglyceride levels (p<0.05), but not cholesterol when compared with control diabetic rat (p>0.05). Andrographolide and purified extract did not appear to give antiatherosclerosis effect.